2023
DOI: 10.1186/s12859-023-05348-3
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic and prognostic role of cuproptosis-related genes in triple negative breast cancer

Abstract: Background This study aimed to observe the potential impact of known cuproptosis-related genes (CRGs) on triple negative breast cancer (TNBC) development, as well as their associated molecular mechanisms, immune infiltration mechanisms and potential therapeutic agents. Results Based on the Cox Proportional Hazard Model, 11 CRGs may be especially important in TNBC development and progression (considered as the Key-TNBC-CRGs). The expression of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The effective rate of the experimental group with the treatment of radioactive seed 125 I implantation under CT guidance was statistically higher than in the control group with conventional therapy.…”
Section: Iodinementioning
confidence: 72%
See 3 more Smart Citations
“…The effective rate of the experimental group with the treatment of radioactive seed 125 I implantation under CT guidance was statistically higher than in the control group with conventional therapy.…”
Section: Iodinementioning
confidence: 72%
“…It is involved in the cellular metabolism as a catalytic cofactor in the regulation of energy production, oxygen transport, iron storage, signal transduction, and other intracellular processes. Even a small increase in Cu concentration in the body can cause severe toxicity, oxidative stress, initiation, and promotion of carcinogenesis [124,125]. The 2022 case-control study by Barartabar et al showed that the Cu levels (p = 0.0001) in tumor tissue were significantly higher than in tumor margin tissue in 40 women with a histologically confirmed diagnosis of invasive ductal carcinoma [122].…”
Section: Coppermentioning
confidence: 99%
See 2 more Smart Citations
“…CRGs exhibit a close association with tumor immunity in TNBC and can serve as predictive markers for patient prognosis [ 9 ]. Current research endeavors have concentrated on exploring the potential prognostic significance of CRGs in TNBC, demonstrating a close correlation between CRGs and tumor immunity in TNBC [ [9] , [10] , [11] ]. However, miRNAs associated with TNBC have not been explored to date.…”
Section: Introductionmentioning
confidence: 99%